Remember Leptospirosis: two cases report - Seara, Vera; Mandim, Andreia; Vasconcelos, Joana; Moça, Rita (Brazilian Journal of Case Reports, 2022)
Leptospirosis has a wide variety of clinical manifestations, from asymptomatic to vital organ involvement. Its significant morbidity highlights the importance of recognizing and identifying how leptospirosis can be acquired and transmitted. With adequate management, the disease can be treated with no complications. The authors describe two patients, a couple from a rural area in Portugal, presenting with different manifestations of the same disease a month apart between hospitalizations. Both experienced kidney and liver dysfunction, and although having different therapeutic approaches, both had a favorable evolution. Recognition of leptospirosis based on clinical symptoms and specific laboratory clues may allow early initiation of therapy. Occupational exposure is a significant risk factor. Vaccination and awareness programs are essential for reducing the risk.